Numerical Simulation Flow Analyses around a Cylinder under Transversal and Eight Trajectories - Pinto, L C; Boeira, L; Silvestrini, J H; Schettini, E B C (2009 Third Southern Conference on Computational Modeling, 2009)
This work aims to study a two-dimensional incompressible flow around a cylinder in forced movement in order to understand the phenomena that occur in cylindrical structures under periodic oscillation using the Direct Numerical Simulation technique. The simulations were taken using the computational code named Incompact3d. It was used the Reynolds Number as 400 in all simulations. The trajectories transversal and eight shapes were simulated for a range of displacement amplitude. The Navier-Stokes and continuity equations were used to discretize the flow in a Cartesian mesh. It was used the third-order Runge-Kutta scheme with low-storage for the pass-time and the body was represented by the virtual boundary method. The temporal mean of the drag and lift coefficients and vortex shedding mode were computed. The results show large variations of the mean lift coefficient with the amplitude displacement for all trajectories, and so altering the vortex shedding mode. The 2S mode was observed for simulations with transversal trajectories, except for amplitude of 0.55D, which presented the 2P mode. Simulations with eight trajectory presented 2P mode in most cases, and for certain amplitudes the periodic shedding modes were not observed.